Sounds in Fawasil Verses and Its Relation to Meaning: Phonetic Studies of the Qur'an in Q.S al-Buruj - Rahma, Raisya Miftakhul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This paper is entitled